Demand effects of fiscal policy since 2008. (January 2019) - Stockhammer, Engelbert; Qazizada, Walid; Gechert, Sebastian
Abstract : The Great Recession of 2007–2009 has led to controversies about the role of fiscal policy. Academically this has translated into renewed interest in the effects of fiscal policy. Several studies have since suggested that fiscal multipliers are substantially larger in downswings or depressions than in upswings. In terms of economic policy reactions, countries have differed substantially in their fiscal stance. It is an important open question how big the impact of these policies on economic growth has been. The paper uses the regime-dependent multiplier estimates byQazizada and Stockhammer (2015) and byGechert and Rannenberg (2014) to calculate the demand effects of fiscal policy for Germany, the USA, the UK, Greece, Ireland, Italy, Portugal and Spain since 2008. This allows us to assess to what extent fiscal policy explains different economic performances across countries. We find expansionary fiscal policy in 2008–2009 in all countries, but since 2010 fiscal policies have differed. While the fiscal effect was roughly neutral in Germany, the UK and the USA, it was large and negative in Greece, Ireland, Italy, Portugal and Spain.